Cortical and Deep Gray Matter Perfusion Associations With Physical and Cognitive Performance in Multiple Sclerosis Patients - Jakimovski, Dejan; Bergsland, Niels; Dwyer, Michael G.; Traversone, John; Hagemeier, Jesper; Fuchs, Tom A.; Ramasamy, Deepa P.; Weinstock-Guttman, Bianca; Benedict, Ralph H. B.; Zivadinov, Robert (Frontiers in Neurology, 2020)
Background: Reports suggest presence of cerebral hypoperfusion in multiple sclerosis (MS). Currently there are no studies that examine if the cerebral MS perfusion is affected by presence of cardiovascular comorbidities. Objective: To investigate associations between cerebral perfusion and disease outcomes in MS patients with and without comorbid cardiovascular diseases (CVD). Materials: One hundred three MS patients (75.7% female) with average age of 54.4 years and 21.1 years of disease duration underwent 3T MRI dynamic susceptibility contrast (DSC) imaging and were tested with Expanded Disability Status Scale, Multiple Sclerosis Severity Score (MSSS), Timed 25-Foot Walk (T25FW), 9-Hole Peg Test (9HPT) and Symbol Digit Modalities Test (SDMT). Structural and perfusion-based normalized measures of cerebral blood flow (nCBF), cerebral blood volume (nCBV) and mean transit time (MTT) of global, tissue-specific and deep gray matter (DGM) areas were derived. CBV and CBF were normalized by the normal-appearing white matter counterpart. Results: In linear step-wise regression analysis, age- and sex-adjusted, MSSS (R2 = 0.186) was associated with whole brain volume (WBV) (β = −0.244, p = 0.046) and gray matter (GM) nCBF (β = −0.22, p = 0.035). T25FW (R2 = 0.278) was associated with WBV (β = −0.289, p = 0.012) and hippocampus nCBV (β = −0.225, p = 0.03). 9HPT (R2 = 0.401) was associated with WBV (β = 0.195, p = 0.049) and thalamus MTT (β = −0.198, p=0.032). After adjustment for years of education, SDMT (R2 = 0.412) was explained by T2-lesion volume (β = −0.305, p = 0.001), and GM nCBV (β = 0.236, p = 0.013). No differences in MTT, nCBF nor nCBV measures between patients with (n = 42) and without CVD (n = 61) were found. Perfusion-measures were also not able to distinguish CVD status in a logistic regression model. Conclusion: Decreased GM and deep GM perfusion is associated with poorer MS outcomes, but not with presence of CVD.